Innate talent in sport - Joseph Baker; Nick Wattie (Bern Open Publishing, 2018)
Twenty years ago, Howe, Davidson and Sloboda (1998) provided a state of the science review of innate talent. This paper was extremely influential although much has changed in the two decades since it was published. In this review, we revisit Howe et al's assessment and discuss current research on innate talent in sport, a domain that was largely ignored in the original review. After re-evaluating Howe et al's criteria for innate talent we conclude that with the exception of criterion 5 (i.e., talent is domain specific), these criteria are still useful in the context of existing evidence in sport. We subsequently examine two complementary issues: Is the concept of innate talent valid? Does the concept have any utility? We conclude the concept of innate talent is valid but currently has limited utility to those working in high performance sport. We highlight several areas of future research that will ultimately inform the value of innate talent to those working at the frontlines of athlete development.